PERLINDUNGAN HUKUM TERHADAP BURUH WANITA SEKTOR PEKERJA RUMAH TANGGA (PRT) DI KOTA SURABAYA - Muwahid Muwahid (universitas islam darul ulum lamongan, 2017)
Research on the legal protection of women workers housekeeper sector aims to answer the problem; how the legal protection arrangements for a domestic helper in the legislation, how application of legal protection against domestic servants in the city of Surabaya, what obstacles and solutions to the implementation of the legal protection. This study is an empirical law, sources of primary data obtained from the respondents, namely domestic, manpower officials, NGOs. Secondary data source of legislation. Data was collected through interviews, observation, and study documents, while data analysis using inductive thought pattern. The results showed: the setting of legal protection in labor law is limited to formal workers, domestic helpers work (PRT) in the legislation are not categorized as workers, so that their basic rights as workers are not guaranteed. Application of legal protection of women workers sector domestic workers (PRT) in the city of Surabaya is not maximized. Most domestic workers in the city of Surabaya who do not get their rights as workers such as the right to earn wages above the minimum wage city, leave entitlements, social security rights and workplace accidents. factors that affect the application of the maximum no legal protection for women workers sector domestic workers (PRT) in the city of Surabaya is as follows; First, juridical factors. Legally, domestic as normative informal workers do not enter the category of workers under Law No. 13 In 2003, the Second, sociological factors. Sociologically, the implementation constraints of legal protection for domestic workers domestic workers due to low education, economic urgency, domestic practices tend to closed and lack of control of the government.